Modern use of modified Sequencing Batch Reactor in wastewater Treatment - Khan, Afzal Hussain; Rudayni, Hassan Ahmad; Chaudhary, Anis Ahmad; Imran, Mohd; Vambol, Sergij (Ecological Questions, 2022)
If wastes are not properly managed, it may seep into the earth and aquifers, polluting both the surface and the water table. For public health reasons, leachate is considered a major environmental hazard due of its poisonous and hardy components. Because of this, it must be collected and processed adequately before being released into nature. Currently, there is no single unit procedure for appropriate leachate treatment since traditional wastewater treatment techniques are unable to degrade harmful chemicals contained in the leachate to a suitable level. Consequently, there has been an increase in the study of various leachate treatment procedures in order to maximise operational versatility. Various strategies have been used to degrade the leachate based on its properties, discharge requirements, technological possibilities, regulatory restrictions, and cost concerns. Sequencing batch reactor (SBR) treatment systems for landfill leachate were lauded for their operating flexibility, shock load resilience, and high biomass retention in the interest of long-term sustainability for the environment. Therefore, the current work objective is a deeper study of the features of SBR to identify prospects and unresolved problems in this process. The content analysis method of scientific publications from rating journals indexed in Scopus, PubMed, ScienceDirect, ResearchGate, Google Scholar on the totality of the keywords of this study in various combinations was applied; selection and synthesis of the main characteristics SBR to identify gaps in this area and prospects for future research. An in-depth analysis of the benefits and drawbacks of different leachate degrading processes is provided in this article. The role of integrated leachate treatment technologies with SBR was also highlighted. The effects of various materials, techniques, tactics, and configurations on leachate treatment were also explored in the paper. Critiqued SBR system environmental and operational factors were addressed. Readers of this work are expected to get a better understanding of SBR studies for leachate treatment and to use this information as a guide for their own research in this field. It uses the fill and draw activated sludge system with clarifier and intermittent aeration mode, where all the metabolic reactions and the separation of solid-liquid takes place in a unit tank through a timed control sequence in a non-steady state, variable capacity and suspended growth biological wastewater treatment system. The simultaneous nitrification, denitrification, and phosphorus removal are made possible by combining anaerobic and aerobic processes.